An improved programmable grating array based wavefront sensor - Pathak, B (Society of Photo-optical Instrumentation Engineers, 2021)
An improved programmable grating array based wavefront sensor (GAWS) is proposed which is capable of estimating the incident wavefront more accurately, by generating an array of uniform intensity +1 order spots with negligible contribution from unwanted higher order spots. The duty cycle of each grating element of the proposed sensor is effectively varied in order to independently control the intensity of each +1 order spot. Furthermore, random binarisation technique is implemented on the diffraction grating array to reduce the contribution from undesirable higher order spots by disintegrating them into noise. Proof-of-principle simulation results are presented to demonstrate the working of the proposed GAWS in comparison to the conventional GAWS, for non-uniform intensity of the +1 order spots.